THE STRUGGLE OF SCARLET OâHARA TO FIND PURE LOVE IN MARGARET MITCHELâS GONE WITH THE WIND (1936) - Astuti, Lina Try; Apriani, Liza Dwi (LITERARY CRITICISM, 2015)
The research entitled is The Struggle of Scarlet Oâhara to Find Pure Love in Margaret Mitchel Gone With The Wind (1936). The aim of the study is exploringÂ the most dominat of Scarlet Oâhara needs appering Gone With The Wind (1936) and to know the struggles of Scarlet Oâhara in finding her needs in Gone With The Wind (1936). This research applied qualitative method. In this research the writer will describe the collected-data. The writer explore the protagonist character in the novel and use the concept of Abraham Maslowâs five basic hierarchy of needs especially focused on the struggle for love, affection and belongingness also self actualization needs. Based on the analysis, the researcher finds that Scarlet Oâhara struggles to love, affection, belongingness and self actualization because she needs a man to be love, familyâs affection and get many friends. The finding research can be stated that the most dominant of Scarlet Oâhara needsÂ apperingÂ Â Gone With The Wind (1936) is the needs of love, affection, and belongingness to make her life full of joy and happiness.Â Keywords : Struggle, Love, Affection, Belongingness